Сравнение структуры и теплоизоляционных особенностей кожного покрова некоторых видов полевок - Кожуховская, А.Ф. (Вестник зоологии, 1970)
An investigation of the structure of skin and its thermoisolation peculiarities was carried out in the species Microtus arvalis Pall., Arvicola terrestris L. and Ondatra zibethica L. from the Microtinae subfamily which are taxonomically dose but adopted to the water environment to a different degree. They were caught in the Leningrad region during March 1967—1968. It was established that both the structure of the skin and its thermoisolation peculiarities are in a direct dependence on the degree of animal connection with the wetur environment.